FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMAKAIAN KONTRASEPSI KONDOM PADA PASANGAN USIA SUBUR DI WILAYAH KERJA PUSKESMAS CAMPALAGIAN - Muliyana; Reskiawati Azis (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
The research objective: To determine the factors associated with the use of contraceptive condoms in fertile aged couples in the Campalagian Community Health Center. Methods: This study is an analytical survey research with a "Cross Sectional Study" approach where the independent and dependent variables are collected at the same time to obtain information about several factors associated with the use of the condom contraceptive method in reproductive age couples (EFA). Results: The results showed that the results of the analysis using the Chi-square test between knowledge and the low use of condom contraception obtained p value = 0.003 (P value <0.05), which means that Ha is accepted, between side effects and low use of condom contraception, the p value is obtained. = 0.002 (P value <0.05), which means that Ha is accepted, between parity and the low use of condom contraceptives, the value of p = 0.010 (P value> 0.05) means that Ho is rejected. So that statistically it is considered that there is a relationship between knowledge, side effects and the low use of the condom contraceptive method, while parity is considered to have no relationship with the low use of condom contraception. Discussion: family planning is an action that helps husband and wife to avoid unwanted pregnancies, get births that are very desirable, adjust the interval between pregnancies, control the time at birth in relation to the age of the husband and wife and determine the number of children in the family. The fertile period of a woman has a role in the occurrence of pregnancy so that the chances of a woman giving birth are quite high. According